Pengembangan Video Animasi Toontastic Terintegrasi Model Kooperatif STAD pada Pembelajaran PPKn di Madrasah Ibtidaiyah - Maisyaroh Maisyaroh; Novita Hanum; Mukti Kanaya Sidiq (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to develop and assess the feasibility of animated video learning media using Toontastic application, integrated with the Student Teams Achievement Divisions (STAD) cooperative learning model. The development focused on Civics Education (PPKn), specifically on the topic of individual characteristic diversity for fourth-grade students at MIS Darul Hikmah, Medan. This study employed a Research and Development (R&D) approach utilizing the 4D model (Define, Design, Develop, and Disseminate). Product feasibility was evaluated through expert validation and limited field trials. The results indicated that the developed media was categorized as "very feasible." This is evidenced by the material expert validation score of 86 and the media expert validation score of 86. Furthermore, field trials demonstrated high user acceptance, with teacher response reaching a feasibility rate of 85.71% and student response at 85.71%. These findings suggest that Toontastic-based animated video is an effective and appropriate instructional medium to enhance Civics Education learning at the elementary level.